Derivatives usage by non-financial firms in Singapore for hedging purposes. - Fong, Wei Sze. (2008)
This project explores the importance of the use of derivatives in Singapore. Hence, our study aims to understand the type of users, their patterns of usage and the concerns with regards to derivative usage in Singapore.